Effects of low- and high-frequency repetitive transcranial magnetic stimulation on long-latency auditory evoked potentials. (1st November 2018) - Nathou, Clément; Duprey, Emmanuelle; Simon, Gregory; Razafimandimby, Annick; Leroux, Elise; Dollfus, Sonia; Etard, Olivier
Highlights: RTMS modulation effects on motor cortex should not be transposed to temporal cortex. RTMS applied to the temporal cortex can induce remote effects on the frontal cortex. Auditory-ERP could examine neuromodulation effects of rTMS upon the temporal cortex. Abstract: Long-latency auditory event potentials (LLAEPs) involving local and global auditory processes have been investigated to examine the impact of low-frequency (LF) and high-frequency (HF) repetitive transcranial magnetic stimulation (rTMS) on the cortical excitability of the temporal cortex. We hypothesized that both stimulation frequencies have the same modulation effect, in accordance with clinical data showing a reduction in auditory verbal hallucinations (AVHs) after LF and HF temporal rTMS in patients with schizophrenia. With 30 right-handed healthy volunteer participants enrolled in a crossover trial, we analyzed LLAEPs before and after LF- and HF-rTMS of the left temporal cortex. While we observed no changes in latencies, we did observe a similar inhibitory action of both rTMS frequencies on LLAEP amplitudes. Analysis of surface potential maps and cortical generators revealed some differences regarding auditory processes: HF-rTMS produced earlier, more diffuse, and more right-lateralized effects than LF-rTMS. Beyond a local impact, rTMS exerted a remote modulation influence on the frontal cortex that might be involved in attentional processes. This association could explain the therapeutic effect of temporal HF-rTMS on AVH.